Skills Based Interventions terhadap Psikososial Remaja dengan Penyakit Kronik - Putry Nur Faidah; Allenidekania Allenidekania; Dessie Wanda (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the types of skills and the effect of skills-based interventions on the psychosocial impact of adolescents with chronic illnesses. The method used was a systematic review of 12 articles searched through the PROQUEST, Science Direct, ClinicalKey, EBSCO, Taylor & Francis, and Pubmed databases with inclusion criteria for the adolescent population, English articles, quantitative studies, year of publication 2010 – 2022, and full-length essays text. The results showed a diversity of skills and positive effects of skills-based interventions on psychosocial adolescents by reducing psychological distress and increasing adaptive coping, competence, social functioning, and self-efficacy. Types of skills include social skills, coping skills, and self-management. In conclusion, multi-session skills-based interventions by professionals with various skills can be a practical choice of interventions in psychosocial services for adolescents with chronic illnesses. Keywords: Chronic Disease, Psychosocial, Adolescents, Skills Based Interventions